Macroeconomic Factors in Oil Futures Markets - Heath, Davidson (Management Science, 2019)
This paper documents new evidence against perfect risk spanning in crude oil futures, and develops an affine futures pricing model that allows for unspanned macroeconomic factors. Compared to previous estimates, the oil spot premium is more volatile and strongly procyclical, which suggests that previous models miss the majority of variation in oil risk premiums. The estimates reveal a dynamic two-way relationship between oil futures and economic activity: productivity shocks are associated with higher oil prices, while oil price shocks affect economic activity by lowering future consumption spending. Unspanned macro factors also affect the valuation of real options. This paper was accepted by Karl Diether, finance.